Toward a prison theology of California’s ecclesia incarcerate - Sexton, Jason S. (Theology, 2015)
The State of California has been a trendsetter in radical forms of penal policy and mass-incarceration in Western societies. As such California’s prison state and its governance structures demand careful scrutiny. These governance structures are both formal and informal, manifesting different power structures at play within the system. Any proper theological account of such phenomena needs to reckon not only with these extant structures but also with the incarcerate ecclesia, the prison church. The present article aims to highlight the reality of this community within the California prison settings (with relevance to other penal contexts), a community that is locally supernaturally constituted, inter-racial, spatially transcendent and transformational, displaying the power of the gospel among its participants. In this way, the incarcerated church subversively fulfils the aims of the other formal and informal governance structures, both sanctioned by the State and manifest in prison gangs.